Expansion Pulmonary Therapy in Blood Oxygenation and Lactate Serum Level in Postoperative Cardiac Surgery - Oliveira,Silvana Souza (2018)
Abstract Background: Cardiovascular and pulmonary complications often occur in the immediate post- surgery period and may be prevented and/or treated with lung expansion techniques. Objective: To evaluate the efficacy of lung expansion techniques in serum arterial lactate levels and oxygenation in patients in this surgical recovery phase. Method: A prospective and analytical study was carried out in postoperative cardiac surgery patients, hemodynamically stable. Measurements of artery lactate levels and partial pressure of oxygen were obtained from arterial blood samples drawn before and after lung expansion techniques, including alveolar recruiting maneuver and intermittent positive pressure breathing. Results: 40 patients with average age of 51.1 ± 14.9 years, 55% female, were included. It is possible to observe the statistically significant difference (p < 0.05) in the comparison between values of baseline and post-operative arterial lactate, oxygen level, oxygen saturation/fraction of inspired oxygen in both procedures. In relation to the outcome of oxygen blood pressure, only the group on intermittent positive pressure breathing achieved significant improvement. Conclusion: The lung expansion techniques used have contributed with the reduction of lactate level, improvement in oxygenation and oxygen saturation in this population, but did not alter intensive care unit length of stay.